COMPARISON OF SGD, RMSProp, AND ADAM OPTIMATION IN ANIMAL CLASSIFICATION USING CNNs - Desi Irfan; Teddy Surya Gunawan; Wanayumini Wanayumini (Universitas Respati Yogyakarta, 2023)
Many measures have been taken to protect endangered species by using